2001
DOI: 10.1590/s1519-69842001000400007
|View full text |Cite
|
Sign up to set email alerts
|

Short-term variability of copepod abundance in Jurumirim Reservoir, São Paulo, Brazil

Abstract: Short-term variability in composition and abundance of copepod populations were studied during the dry (winter) and rainy (summer) seasons, at the dam region of Jurumirim Reservoir, São Paulo, Brazil. An intensive sampling program was carried out during 30 days in each period of the year. Samples and measurements were taken every other day at 0, 5, 10, 15, 20 and 25 m depths. The relationship between variability of the populations and some environmental factors was analyzed. The main species were: Argyrodiapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
3
14
1
5
Order By: Relevance
“…In the other hand, Velho et al (2001) found only one calanoid (Notodiaptomus iheringi) in 21 sampling stations along the Corumbá Reservoir, including the river (upstream and downstream from the dam), tributaries, and lateral arms. In this study, Notodiaptomus iheringi reached small densities although it was frequent and, attained high densities in the lacustrine zone of Jurumirim Reservoir (Nogueira & Panarelli, 1997;Panarelli et al, 2001;Nogueira, 2001). Cyclopoids were represented by Mesocyclops and Thermocyclops, the latter genus being the most abundant.…”
Section: Discussionmentioning
confidence: 51%
“…In the other hand, Velho et al (2001) found only one calanoid (Notodiaptomus iheringi) in 21 sampling stations along the Corumbá Reservoir, including the river (upstream and downstream from the dam), tributaries, and lateral arms. In this study, Notodiaptomus iheringi reached small densities although it was frequent and, attained high densities in the lacustrine zone of Jurumirim Reservoir (Nogueira & Panarelli, 1997;Panarelli et al, 2001;Nogueira, 2001). Cyclopoids were represented by Mesocyclops and Thermocyclops, the latter genus being the most abundant.…”
Section: Discussionmentioning
confidence: 51%
“…Coincidence in major abundance peaks of these species was not observed, indicating a temporal segregation between them. As observed by Panarelli et al (2001), T. minutus (Lowndes, 1934) was more abundant in the dry period.…”
Section: Zooplankton Composition and Seasonal Fluctuationmentioning
confidence: 57%
“…In terms of temporal dynamics, the monthly variation of the thermal regime and stability, oxygen deficit (Henry 1992(Henry , 1993a) and primary production by phytoplankton (Henry, 1993b;Henry et al, 2006); the influence of hydrological seasonality on seston sedimentation and transport (Henry and Maricato, 1996); the space-temporal variation of phytoplankton (Henry et al, 1998), zooplankton (Nogueira, 2001), and physical-chemical variables , have all been analyzed. Shorter periods of time have also been considered for zooplankton studies in Jurumirim: short term (weekly) variability in rainy and dry periods (Panarelli et al, 2001) and vertical migration in nictemeral cycles (Nogueira and Panarelli, 1997). Some interdecade information (70's and 80's) on the composition and abundance of zooplankton has also been provided (Sampaio et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, the most studied reservoir ecosystems are located in the Southeast, South and West regions, such as the Paranoá in Brasilia, Pampulha in Minas Gerais, Monte Alegre and Jurumirim in São Paulo and Segredo in Paraná. Many studies have been carried out in these regions on the composition and diversity of zooplankton, especially concerning the Rotifera and Crustacea (Cabianca and Sendacz, 1985;MatsumuraTundisi et al, 1990;Arcifa et al, 1998;Güntzel and Rocha, 1998;Nogueira, 2001;Panarelli et al, 2001;Mitsuka and Henry, 2002).…”
Section: Introductionmentioning
confidence: 99%